1974
DOI: 10.1007/bf00880852
|View full text |Cite
|
Sign up to set email alerts
|

PR aside: Initial results from NIMH's service program evaluation studies

Abstract: NIMH's program evaluation studies assess the exlent and conditions utzder which services are provided according to community mental health center process goals of increasing quanti(v and range of service, decreasing use of state hospitals, responsiveness to needs, accessibiliO,, equiO', communiO, participation, and continuity and effectiveness of services. Completed contracts, annual inventories, and site visits indicate: (a) some developmeTzt of methods .for measuring processes," (b) evidence that the Centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Community members may function at less than optimal levels rather than seek psychiatric treatment because of the stigma associ ated with doing so (Lee, Gianturco, & Eisdorfer, 1974;Windle, Bass, & Taube, 1974). Finally, public reluctance to have those with mental disorders in their midst hampers efforts to make psychiatric care more accessible, effective, and cost efficient (Aviram & Segal, 1973;Baron, 1981;Kiesler, 1982aKiesler, , 1982bKiesler et al, 1983;Morrison, 1980;Scott, Balch, & Flynn, 1983;Williams, Bellis, & Wellington, 1980).…”
mentioning
confidence: 96%
“…Community members may function at less than optimal levels rather than seek psychiatric treatment because of the stigma associ ated with doing so (Lee, Gianturco, & Eisdorfer, 1974;Windle, Bass, & Taube, 1974). Finally, public reluctance to have those with mental disorders in their midst hampers efforts to make psychiatric care more accessible, effective, and cost efficient (Aviram & Segal, 1973;Baron, 1981;Kiesler, 1982aKiesler, , 1982bKiesler et al, 1983;Morrison, 1980;Scott, Balch, & Flynn, 1983;Williams, Bellis, & Wellington, 1980).…”
mentioning
confidence: 96%
“…To be properly understood these results should be put in the context of all other evaluations. Most of the other evaluation studies found that centers were making progress in the program's various service process goals, although none of these goals has been completely achieved (Windle, Bass, & Taube, 1974). Further, the reduction of state hospital utilization is a gross program goal that needs increasing refinement as the population of state hospitals declines (Taube, 1974) and state hospital services improve (Taube, 1970).…”
Section: Discussionmentioning
confidence: 95%
“…Most of the other evaluation studies found that centers were making progress in the program's various service process goals, although none of these goals has been completely achieved (Windle, Bass, & Taube, 1974). Further, the reduction of state hospital utilization is a gross program goal that needs increasing refinement as the population of state hospitals declines (Taube, 1974) and state hospital services improve (Taube, 1970). In addition, this paper has examined only a single mechanism for achieving the Community Mental Health Centers Program goals, the existence of federally funded centers.…”
Section: Discussionmentioning
confidence: 95%
“…Reliance on a voluntary model is concerning, as prior PPI failures can be traced in part to challenges getting an adequate number of consumers to participate. 16 Furthermore, despite statutory requirements that local Healthwatch must be “inclusive and reflect the diversity of the community it serves,” 13 costs inherent in participation are likely to pose a barrier to those who may be lower income or otherwise disadvantaged. Consequently, these individuals may find that their voice is excluded from the discussion altogether.…”
mentioning
confidence: 99%